Legal professionals in white-collar crime: knowing, thinking and acting - Trombini, Maria Eugenia (Springer Fachmedien Wiesbaden, 2023)
Introduction -- Theoretical basis for studying legal professionals in white-collar crime -- Research design -- How do legal professionals think? -- How do legal professionals decide? -- Additional factors of explanations -- How autonomous has the legal elite been in respect to the state and the market? -- Conclusion.
Keywords: Hochschulschrift; Korruption; Wirtschaftskriminalität; Jurist; Brasilien